2017
DOI: 10.1177/1748895817734590
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a perpetrator-focused partnership approach to tackling domestic abuse: The opportunities and challenges of criminal justice localism

Abstract: This article reports on a perpetrator focused partnership approach to tackling domestic abuse. The package of interventions includes an identification tool and a unique multiagency partnership approach to violence prevention and tackling abuse through perpetrator focused early interventions. An overview of the key outcomes and issues emerging from this innovative package and partnership approach in one policing area in England is offered. Our discussion focuses on issues relating to the development of the co-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…uneven training and expertise with regard to the practice of risk assessment compounded by different professional vantage points, dynamic policy contexts and increasing limitations upon resources, see Medina Ariza et al, 2016;Robinson, 2010;Robinson et al, 2018), our study clearly emphasises the benefits of partnership working, as each pilot was able to pool i tellige e from multiple data sources in order to provide a more holistic picture of both the victim and the perpetrator. These findings echo those of Davies and Biddle (2018) who noted that a a ge of age ies a d i di idualswith diverse priorities, professional backgrounds and practicescan work together to safeguard victims and tackle serial perpetrators of domestic abuse p.16). Indeed, Murphy et al (1998) noted that the benefits of adopting a multi-agency approach to tackling domestic abuse can offset the limitations of sole reliance upon police interventions because they represent just one element of a complex process that includes court prosecutions, probation monitoring, court-mandated perpetrator programmes, and victim services.…”
Section: Resultssupporting
confidence: 77%
“…uneven training and expertise with regard to the practice of risk assessment compounded by different professional vantage points, dynamic policy contexts and increasing limitations upon resources, see Medina Ariza et al, 2016;Robinson, 2010;Robinson et al, 2018), our study clearly emphasises the benefits of partnership working, as each pilot was able to pool i tellige e from multiple data sources in order to provide a more holistic picture of both the victim and the perpetrator. These findings echo those of Davies and Biddle (2018) who noted that a a ge of age ies a d i di idualswith diverse priorities, professional backgrounds and practicescan work together to safeguard victims and tackle serial perpetrators of domestic abuse p.16). Indeed, Murphy et al (1998) noted that the benefits of adopting a multi-agency approach to tackling domestic abuse can offset the limitations of sole reliance upon police interventions because they represent just one element of a complex process that includes court prosecutions, probation monitoring, court-mandated perpetrator programmes, and victim services.…”
Section: Resultssupporting
confidence: 77%
“…Each of the above listed initiatives had also been evaluated or reviewed. The MATAC was independently evaluated (see Davies and Biddle 2017) iii whilst the EIP and Operation Kyleford were subject to internal review which generated performance and/or case study data. A police review of the EIP indicates that over 55% of EIP cases resulted in no further reported incidents, with case studies also illustrating the added value of the initiative.…”
Section: Police (Ii)mentioning
confidence: 99%
“…This suggests that shifting the cultural environment within policing such that it can become more receptive to innovation, trialling new projects, and critical reflectioninherent features of social scientific practiceis possible, albeit in this case this was only achieved because the project was identified as outside the mainstream of police activity. (See also Davies and Biddle, 2017). Fourth, experience as craft refers to knowledge as complex, tacit, skill and wisdom based.…”
Section: Collaborative and Co-produced Researchmentioning
confidence: 99%
“…From this point of view, other people become a repository for these parts of violent adults, so that any change, departure or non-response threatens their sense of self and potentially causes self-disintegration. This mechanism creates a hostile context around men, but, at the same time, inevitably keeps men tied to their companions [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the article “Domestic Violence Perpetrator Programs in Europe, Part II A Systematic Review of the State of Evidence” [ 44 ], the authors find that the assessment of the treatment of the authors of Domestic violence in Europe needs to be improved and programs should become more tailored to the characteristics of the participants. This perspective clashes with the vision that funds spent on men’s care are perceived as “diverted” from more urgent priorities, especially considering the need to protect women and take care of children who have been exposed to violence [ 33 ]. Differentiating motivations, reasons, functions, justifications and contexts is the challenge that researchers have to face in this sector.…”
Section: Introductionmentioning
confidence: 99%